2016
DOI: 10.5337/2016.212
|View full text |Cite
|
Sign up to set email alerts
|

Reviving the Ganges water machine: potential and challenges to meet increasing water demand in the Ganges River Basin

Abstract: The publications in this series cover a wide range of subjects-from computer modeling to experience with water user associations-and vary in content from directly applicable research to more basic studies, on which applied work ultimately depends. Some research reports are narrowly focused, analytical and detailed empirical studies; others are wide-ranging and synthetic overviews of generic problems.Although most of the reports are published by IWMI staff and their collaborators, we welcome contributions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The total renewable water resources in the Ganges Basin amount to about 552 km 3 . Between 20% and 40% of the water resources in the Ganges River Basin is used (Amarasinghe et al 2016a(Amarasinghe et al , 2016bChinnasamy et al 2017) mainly for irrigation, while the Brahmaputra and Meghna rivers remain largely unexploited as they flow through India, because rainfall is sufficient and the terrain is not conducive to large-scale irrigation. According to the systematic classification of the Uttarakhand Environment Protection and Pollution Control Board, water quality in the Ganges River is extremely low, mainly due to contamination by fecal coliform.…”
Section: The Ganges-brahmaputra-meghna (Gbm) River Systemmentioning
confidence: 99%
“…The total renewable water resources in the Ganges Basin amount to about 552 km 3 . Between 20% and 40% of the water resources in the Ganges River Basin is used (Amarasinghe et al 2016a(Amarasinghe et al , 2016bChinnasamy et al 2017) mainly for irrigation, while the Brahmaputra and Meghna rivers remain largely unexploited as they flow through India, because rainfall is sufficient and the terrain is not conducive to large-scale irrigation. According to the systematic classification of the Uttarakhand Environment Protection and Pollution Control Board, water quality in the Ganges River is extremely low, mainly due to contamination by fecal coliform.…”
Section: The Ganges-brahmaputra-meghna (Gbm) River Systemmentioning
confidence: 99%
“…These basins have high aggregated UTFI suitability scores (Table 6) and are located in regions with significant UTFI potential, i.e., East Africa, South Asia and Southeast Asia ( Figure 6; Table 5). Previous basin-level hydrologic studies conducted for the three selected basins reaffirmed the prevalence of flooding (Getahun and Gebre 2015;Mirza et al 2001;Poapongsakorn and Meethom 2012), issues related to drought/water scarcity (Edossa et al 2010;Khan et al 2014;Molle 2002), and seasonal imbalances between water supply and demand (Adeba et al 2015;Amarasinghe et al 2016;Pavelic et al 2012). The Ramganga is distinguishable as the location of a UTFI pilot study (Pavelic et al 2015), and a basin-level modelling analysis indicates high potential for UTFI in this basin (Chinnasamy et al 2018).…”
Section: Characteristics Of the Selected River Basinsmentioning
confidence: 70%
“…In overexploited areas of India, UTFI could play a critical role in national-level programs that aim to increase water availability for irrigation, decrease overexploitation and increase resilience to climate change, e.g., National ). In the case of the Ganges River Basin, capturing excess water during the monsoons within the upper and middle parts of the basin (e.g., in the Indian states of Uttar Pradesh and Haryana), which are intensively irrigated with groundwater, would also help mitigate annual floods in the lower parts of the basin (e.g., in states such as Bihar and Jharkhand) (Amarasinghe et al 2016). There is already a sufficiently strong case for UTFI in India with the government identifying UTFI as a strategic approach and envisaging investments in one -and potentially more -district-level irrigation plans over the current 5-year planning cycle (Gangopadhyay et al 2018).…”
Section: Selected Regional Priorities and Entry Points For Utfimentioning
confidence: 99%
“…In Table 7. If there is no sign after values in the table then, the significance level is greater than 0.1 (Amnell et al, 2002). this study, three significant seasons are identified and hence the water quality data are organized into three groups: premonsoon season (February-May), monsoon season (June-September) and postmonsoon season (October-January).…”
Section: Trend Analysis On Monthly Water Quality Datamentioning
confidence: 96%
“…Ganga River is extremely significant to its inhabitants as it supports various important services, such as the following: (i) being a source of irrigation for farmers in agriculture and horticulture, (ii) providing water for domestic and industrial purposes in urban areas, (iii) being a source of hydropower, (iv) serving as a drainage system for waste and helping in pollution control, (v) acting as a support system for terrestrial and aquatic ecosystems, (vi) providing religious and cultural services, (vii) helping in navigation, (viii) supporting fisheries and other livelihood options, etc. (Amarasinghe et al, 2016;SoE report, 2012;Watershed Atlas of India, 2014). However, for the past few decades the Upper Ganga River basin (UGRB) has experienced rapid growth in population, urbanization, industrialization, infrastructure development activities and agriculture.…”
Section: Introductionmentioning
confidence: 99%